Automatic document clustering and indexing of multiple documents using KNMF for feature extraction through Hadoop and lucene on big data - Laxmi Lydia E.; Sharmili N.; Nguyen P.T.; Hashim W.; Maseleno A. (Mattingley Publishing, 2023)
Automatic indexing; Big data; Cluster analysis; Extraction; Factorization; Indexing (of information); Information retrieval; K-means clustering; Natural language processing systems; Open source software; Open systems; Pattern matching; Software quality; Software testing; Text mining; Hadoop; Key phrase extractions; Map-reduce; Pattern-matching technique; Porters; Pre-processing algorithms; Software environments; Unlabeled; Matrix algebra